2014
DOI: 10.14712/18059694.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Variations of the Superficial Jugular Veins: Case Report and Clinical Relevance

Abstract: The jugular venous system constitutes the primary venous drainage of the head and neck. It includes a profundus or subfascial venous system, formed by the two internal jugular veins, and a superficial or subcutaneous one, formed by the two anterior and two external jugular veins. We report one case of unilateral anatomical variations of the external and anterior jugular veins. Particularly, on the right side, three external jugular veins co-existed with two anterior jugular veins. Such a combination of venous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 18 publications
1
28
0
1
Order By: Relevance
“…In the current literature, variations of the jugular veins have been well reported. Paraskevas et al [4] reported a rare case where three external jugular veins were found to co-exist with two anterior jugular veins. In contrast, another case report reported absence of the left EJV.…”
Section: Discussionmentioning
confidence: 99%
“…In the current literature, variations of the jugular veins have been well reported. Paraskevas et al [4] reported a rare case where three external jugular veins were found to co-exist with two anterior jugular veins. In contrast, another case report reported absence of the left EJV.…”
Section: Discussionmentioning
confidence: 99%
“…The junction of the posterior division of the retromandibular vein and the posterior auricular vein usually form the EJV that then continues to drain into the subclavian vein [ 3 - 6 ]. The EJV is sometimes absent ipsilaterally or bilaterally, which means that the veins forming the EJV usually drain into the IJV [ 7 - 8 ]. The EJV usually receives distribution from the transverse cervical vein, the anterior jugular vein, the suprascapular vein, and the superficial cervical vein (Figure 1 ).…”
Section: Reviewmentioning
confidence: 99%
“…Additionally, a double EJV emerging from the parotid gland as two independent veins has been described [ 11 ]. The presence of three right-sided EJVs running in a parallel fashion and draining into the right subclavian vein in a male cadaveric specimen was reported [ 8 ]. Moreover, in this cadaver, there were two anterior jugular veins that drained into the right brachiocephalic vein.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations